Self-compacting concrete and preparation method thereof
By adding corn coin particles, sisal fibers and sodium alginate to the self-finished concrete, and adopting specific treatment methods and mixing sequences, the balance problem between the fluidity and segregation resistance of self-finished concrete is solved, achieving higher segregation resistance and better construction performance.
Patent Information
- Application Number
- CN202411079539.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-08-07
AI Technical Summary
During the pumping and pouring of self-contained concrete, it is difficult to achieve a good balance between fluidity and segregation resistance, resulting in segregation phenomenon that is prone to segregation during the curing process, affecting the overall performance.
By adding corn cob particles, sisal fibers and sodium alginate to the self-finished concrete, and using specific treatment methods and mixing sequences, a special structure is formed to enhance the bonding and segregation resistance inside the concrete.
It is achieved to improve the segregation resistance without affecting the flowability of the concrete, thereby ensuring that the concrete can better fill the mold during the pouring process, reduce pores, and improve compactness and strength.
Smart Images

Figure BDA0004983310130000071 
Figure BDA0004983310130000081 
Figure BDA0004983310130000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of concrete, and more particularly, to a self-compacting concrete and a preparation method thereof. Background Art
[0002] With the continuous development of modern construction technology, concrete, as one of the most important building materials, is also expanding its performance and application range. Among them, self-compacting concrete (SCC) is a high-performance concrete that can automatically flow and densely fill every corner of the formwork under its own gravity to form a uniform and dense structure without relying on external forces such as vibration. This characteristic enables self-compacting concrete to exhibit excellent working performance during the pouring process, which not only simplifies the construction process, improves production efficiency, but also reduces construction costs. It has strong resistance to vibration interference during the coagulation and hardening process, and is particularly suitable for engineering structures with large pouring volume, large pouring depth, dense reinforcement, and complex structure.
[0003] There is a delicate balance between fluidity and resistance to segregation during concrete pumping. When concrete has excellent fluidity, it is easier to pump through pumping equipment, but this high degree of fluidity may also lead to a weakening of the bond between the materials inside the concrete during the curing process. This weakened bond makes the concrete more prone to segregation, that is, the uneven distribution of coarse aggregate and mortar inside the concrete, thus affecting the overall performance of the concrete.
[0004] On the contrary, if the concrete shows good bonding between materials during pouring, it helps prevent the stratification of coarse aggregate and mortar and ensure the uniformity of the internal structure of the concrete. However, when the concrete is too viscous, its fluidity will be reduced accordingly, which will directly affect the efficiency of pumping and increase the difficulty of pumping. At the same time, due to insufficient fluidity, it may be difficult for the concrete to fully fill the formwork during the pouring process, resulting in more pores inside the concrete, which will reduce the density and strength of the concrete.
[0005] Therefore, there is room for improvement. Summary of the invention
[0006] In order to improve the anti-segregation property of self-compacting concrete without affecting the fluidity of the self-compacting concrete, the present application provides a self-compacting concrete and a preparation method thereof.
[0007] In a first aspect, the present application provides a self-compacting concrete, which adopts the following technical solution:
[0008] A self-compacting concrete, comprising the following raw materials in parts by weight: 235-260 parts of cement, 120-160 parts of mineral admixture, 750-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 5-10 parts of admixture, 148-160 parts of water, 5-10 parts of
[0009] Sisal fiber, 10-20 parts corn cob particles, 1-5 parts sodium alginate.
[0010] Preferably, the self-compacting concrete comprises the following raw materials in parts by weight: 245-255 parts of cement, 130-145 parts of mineral admixture, 765-780 parts of fine aggregate, 1000-1100 parts of coarse aggregate, 7-9 parts of admixture, 150-158 parts of water, 6.5-8 parts of sisal fiber, 13.5-18 parts of corn cob particles, and 1.5-3.5 parts of sodium alginate.
[0011] First, the porous structure of corncob particles not only provides additional surface area for concrete, but also allows water and air in the concrete to flow and distribute better during the pouring process. This porosity also helps reduce the density of concrete while improving thermal and sound insulation properties. When corncob particles are evenly distributed in concrete, they act like tiny "anchor points" that help form tighter connections between particles inside the concrete.
[0012] The addition of sisal fiber further enhances this bonding effect. With its excellent bonding and toughness, sisal fiber can effectively "weave" the internal particles of concrete, and some sisal fibers can penetrate the corncob particles to form a more stable and coherent network structure. This network structure not only improves the crack resistance and durability of concrete, but also absorbs and disperses stress through the stretching and deformation of the fibers when the concrete is subjected to external forces, thereby reducing the generation and expansion of cracks.
[0013] As a natural polymer compound, sodium alginate plays the role of "adhesive" in concrete. It can react with the moisture in concrete to form a gelatinous structure, which can tightly wrap the corncob particles penetrated by sisal fibers to form a special structure that can prevent them from floating or moving. At the same time, sodium alginate can also form a stable chemical bond with sisal fibers, further enhancing the stability of the internal structure and special structure of concrete. This stability can effectively improve the compressive strength of concrete and improve the performance stability of concrete.
[0014] The special structure formed by sodium alginate, sisal fiber and corncob particles enhances the connectivity of the raw materials in the system, effectively improves the internal bonding force, and makes the self-compacting concrete more resistant to segregation.
[0015] More importantly, the introduction of these special structures does not affect the fluidity of concrete. On the contrary, they optimize the arrangement and distribution of particles inside the concrete, allowing the concrete to flow and fill the mold better during the pouring process. This good dynamic balance between fluidity and anti-segregation allows self-compacting concrete to have good construction performance while maintaining high performance.
[0016] Preferably, the corncob particles have a particle size of 2-4 mm.
[0017] By adopting the above technical solution, the particle size of the corncob particles is further limited, so that they can better cooperate with sisal fiber and sodium alginate in the system, thereby forming a more stable special structure, so that they can play a more full role in the system.
[0018] Preferably, the corncob particle processing method comprises the following steps:
[0019] Step a: treating corn cobs at 200-300° C. for 30-60 min to obtain calcined corn cobs;
[0020] Step b: soaking the calcined corn cobs in water to obtain water-soaked corn cobs;
[0021] Step c: soaking the water-soaked corn cobs in an alkaline solution to obtain alkaline-soaked corn cobs;
[0022] Step d: crushing the alkali-soaked corn cobs to obtain corn cob particles.
[0023] Corncobs contain a large amount of sugars and other organic substances, which react with cement hydration products during the preparation and hardening of concrete, slowing down the hydration process of cement. Cement hydration is a key step in concrete hardening, and therefore directly affects the strength and other physical properties of concrete. Therefore, the organic substances in corncobs will significantly reduce the compressive strength of concrete, thereby affecting its structural stability and service life. Secondly, cement hydration in concrete releases alkaline substances such as calcium hydroxide, which react chemically with lignocellulose compounds in corncobs and destroy their structure. Lignocellulose is one of the main sources of corncob strength, and the destruction of its structure will lead to a significant reduction in the strength of corncob aggregates. This reduction in strength will further affect the compressive strength and other mechanical properties of concrete. Finally, another important characteristic of corncobs is the volume change when it absorbs and loses water. In concrete, this volume change will lead to a reduction in the bond strength between corncobs and the concrete matrix. When corncobs absorb water, their volume expands, generating internal stress and destroying the bond with the concrete matrix. Conversely, when corncobs lose water, their volume shrinks, creating voids that also weaken their connection to the concrete matrix. This reduction in bond strength further affects the strength and durability of the concrete.
[0024] In order to solve the above problems, the present application performs a specific treatment on corn cobs, which can effectively reduce the soluble organic matter, sugars and impurities in the corn cobs, significantly reduce the effect of organic matter on cement hydration, and thus improve the compressive strength of concrete. In addition, the specific soaking operation can also make the corn cobs absorb water and swell, reducing the volume change in concrete. Although the alkaline environment will destroy the lignocellulose structure in the corn cobs, the appropriate alkali soaking treatment can remove the lignin and other impurities on the surface of the corn cobs and improve its bonding performance with the concrete matrix. The specifically prepared corn cob particles can produce a special combination with sisal fiber and sodium alginate. Preferably, when the step c uses an alkaline solution to soak the water-soaked corn cobs, the microwave power is 100-150W for 30-60s, and the microwave treatment is repeated 1-2 times; then it is allowed to soak for 1-2h to obtain the alkaline soaked corn cobs.
[0025] By adopting the above technical solution, when alkali soaking corn cobs, microwave treatment with specific power and time can be used to effectively change the surface structure of the corn cobs, thereby making it easier to remove impurities such as sugars in the corn cobs and eliminate the adverse effects of corn cobs on concrete.
[0026] Preferably, the mass ratio of the water-soaked corn cobs to the alkali in the alkali solution is 1:(0.01-0.05).
[0027] By adopting the above technical solution, the mass ratio of corn cobs to alkali is further limited, so as not to excessively damage the corn cobs and not to affect the subsequent special combination of corn cob particles with sisal fibers and sodium alginate, thereby maximizing the compressive strength, fluidity and segregation resistance of self-compacting concrete.
[0028] In a second aspect, the present application provides a method for preparing self-compacting concrete, which adopts the following technical solution:
[0029] A method for preparing self-compacting concrete comprises the following steps:
[0030] Step 1: Mix cement, mineral admixture, sisal fiber, corncob particles, sodium alginate and water until uniform to obtain a first mixture;
[0031] Step 2: Mix the fine aggregate with the first mixture, and then add the coarse aggregate and mix until uniform, to obtain the second mixture; Step 3: Mix the second mixture with the admixture until uniform, to obtain self-compacting concrete.
[0032] By adopting the above technical solution and mixing various raw materials in a specific order, the cement slurry can be more fully wrapped around the coarse aggregate and fine aggregate, forming a stronger bonding force, giving the self-compacting concrete better working performance and effectively ensuring better fluidity.
[0033] Preferably, the sisal fiber, corncob particles and sodium alginate are mixed at 650-750 r / min until uniform to obtain a mixture; the mixture is mixed with cement, mineral admixtures, sisal fiber and water until uniform to obtain a first mixture.
[0034] By adopting the above technical solution, sisal fiber, corncob particles and sodium alginate are stirred and mixed at a relatively high speed, fully mixed and evenly dispersed in the system subsequently, so that the coordination effect can be more fully exerted and the anti-segregation property is better.
[0035] In summary, this application has the following beneficial effects:
[0036] 1. This application uses corn cob particles, sisal fibers, and sodium alginate. The combination of the three can form a specific structure, effectively enhance the connectivity of the raw materials in the concrete system, effectively improve the internal bonding force, and thus improve the segregation resistance of the self-compacting concrete.
[0037] 2. Corn cob particles, sisal fibers, and sodium alginate are preferably used in this application, which can effectively optimize the arrangement and distribution of particles inside the concrete, so that the moisture and air in the concrete can flow and distribute better during the pouring process, thereby allowing the concrete to flow better during the pouring process to fill the mold.
[0038] 3. The present application adopts a special method to prepare corn cob particles, which can effectively eliminate the influence of corn cobs on concrete, make the corn cob particles more fully matched with sisal fibers and sodium alginate, thereby improving the performance of self-compacting concrete. DETAILED DESCRIPTION
[0039] The present application is further described in detail below in conjunction with embodiments.
[0040] The raw materials used in the following examples and comparative examples are all commercially available products.
[0041] Example
[0042] Example 1
[0043] A self-compacting concrete comprises the following raw materials: cement, mineral admixture, fine aggregate, coarse aggregate, admixture, water, sisal fiber, corncob particles and sodium alginate.
[0044] The specific amount of each raw material is shown in Table 1.
[0045] The cement is silicate cement with a P.O. of 42.5, the mineral admixtures are fly ash and mineral powder, the fine aggregate is machine-made sand, the coarse aggregate is crushed stone, and the admixture is a slow-setting water-reducing agent.
[0046] The specific model of the slow-setting water-reducing agent used in this embodiment is KH-DO-3, which was purchased from Wuhan Huaxuan High-tech Co., Ltd.
[0047] The machine-made sand used in this embodiment is 1-3 mm, and the crushed stone is 5-15 mm.
[0048] The corncob particles used in this embodiment are prepared by the following steps:
[0049] Step a: calcining corn cobs at 250° C. for 40 minutes to obtain calcined corn cobs.
[0050] Step b: soaking the calcined corn cobs in water, with the mass ratio of calcined corn cobs to water being 1:5, soaking for 2 hours, taking out and drying in hot air to obtain water-soaked corn cobs.
[0051] Step c: weighing the alkali according to the mass ratio of the water-soaked corncob to the alkali being 1:0.03. In this embodiment, the alkali is sodium hydroxide.
[0052] Weigh water according to the ratio of 1:1 between the mass of soaked corn cobs and water, and dilute the alkali and water to prepare a sodium hydroxide solution for standby use.
[0053] The water-soaked corn cobs were immersed in a sodium hydroxide solution, and treated at a microwave power of 120 W for 45 seconds, with a rest period of 30 seconds, and the microwave treatment was repeated twice; and then the corn cobs were allowed to stand and soak for 1.5 hours.
[0054] After taking out, dry in hot air to obtain alkaline soaked corn cob.
[0055] Step d: crushing the alkaline soaked corn cob to obtain corn cob particles, wherein the particle size of the corn cob particles is controlled to be 2-4 mm.
[0056] The present application also provides a method for preparing self-compacting concrete, comprising the following steps:
[0057] Step 1: Mix sisal fiber, corncob particles and sodium alginate at 700 r / min and stir until uniform to obtain a mixture.
[0058] Step 2: Mix cement, mineral admixture, mixture and water, and stir until uniform to obtain a first mixture.
[0059] Step 3: Mix the fine aggregate with the first mixture and stir until uniform.
[0060] Then continue to add coarse aggregate and mix until uniform to obtain the second mixture.
[0061] Step 4: Mix the second mixture with the admixture and stir until uniform to obtain self-compacting concrete.
[0062] Example 2
[0063] A self-compacting concrete comprises the following raw materials: cement, mineral admixture, fine aggregate, coarse aggregate, admixture, water, sisal fiber, corncob particles and sodium alginate.
[0064] The specific amount of each raw material is shown in Table 1.
[0065] The cement is silicate cement with a P.O. of 42.5, the mineral admixtures are fly ash and mineral powder, the fine aggregate is machine-made sand, the coarse aggregate is crushed stone, and the admixture is a slow-setting water-reducing agent.
[0066] The specific model of the slow-setting water-reducing agent used in this embodiment is KH-DO-3, which was purchased from Wuhan Huaxuan High-tech Co., Ltd.
[0067] The machine-made sand used in this embodiment is 1-3 mm, and the crushed stone is 5-15 mm.
[0068] The corncob particles used in this embodiment are prepared by the following steps:
[0069] Step a: calcining corn cobs at 200° C. for 60 minutes to obtain calcined corn cobs.
[0070] Step b: soaking the calcined corn cobs in water, with the mass ratio of calcined corn cobs to water being 1:5, soaking for 2 hours, taking out and drying in hot air to obtain water-soaked corn cobs.
[0071] Step c: weighing the alkali according to the mass ratio of the water-soaked corncob to the alkali being 1:0.01. In this embodiment, the alkali is sodium hydroxide.
[0072] Weigh water according to the ratio of 1:1 between the mass of soaked corn cobs and water, and dilute the alkali and water to prepare a sodium hydroxide solution for standby use.
[0073] The water-soaked corn cobs were immersed in a sodium hydroxide solution, and treated at a microwave power of 150 W for 30 seconds, followed by a rest period of 30 seconds, and the microwave treatment was repeated twice; and then the solution was allowed to stand and soak for 2 hours.
[0074] After taking out, dry in hot air to obtain alkaline soaked corn cob.
[0075] Step d: crushing the alkaline soaked corn cob to obtain corn cob particles, wherein the particle size of the corn cob particles is controlled to be 2-4 mm.
[0076] The present application also provides a method for preparing self-compacting concrete, comprising the following steps:
[0077] Step 1: Mix sisal fiber, corncob particles and sodium alginate at 750 r / min and stir until uniform to obtain a mixture.
[0078] Step 2: Mix cement, mineral admixture, mixture and water, and stir until uniform to obtain a first mixture.
[0079] Step 3: Mix the fine aggregate with the first mixture and stir until uniform.
[0080] Then continue to add coarse aggregate and mix until uniform to obtain the second mixture.
[0081] Step 4: Mix the second mixture with the admixture and stir until uniform to obtain self-compacting concrete.
[0082] Example 3
[0083] A self-compacting concrete comprises the following raw materials: cement, mineral admixture, fine aggregate, coarse aggregate, admixture, water, sisal fiber, corncob particles and sodium alginate.
[0084] The specific amount of each raw material is shown in Table 1.
[0085] The cement is silicate cement with a P.O. of 42.5, the mineral admixtures are fly ash and mineral powder, the fine aggregate is machine-made sand, the coarse aggregate is crushed stone, and the admixture is a slow-setting water-reducing agent.
[0086] The specific model of the slow-setting water-reducing agent used in this embodiment is KH-DO-3, which was purchased from Wuhan Huaxuan High-tech Co., Ltd.
[0087] The machine-made sand used in this embodiment is 1-3 mm, and the crushed stone is 5-15 mm.
[0088] The corncob particles used in this embodiment are prepared by the following steps:
[0089] Step a: calcining corn cobs at 300° C. for 30 minutes to obtain calcined corn cobs.
[0090] Step b: soaking the calcined corn cobs in water, with the mass ratio of calcined corn cobs to water being 1:5, soaking for 2 hours, taking out and drying in hot air to obtain water-soaked corn cobs.
[0091] Step c: weighing the alkali according to the mass ratio of the water-soaked corncob to the alkali being 1:0.05. In this embodiment, the alkali is sodium hydroxide.
[0092] Weigh water according to the ratio of 1:1 between the mass of soaked corn cobs and water, and dilute the alkali and water to prepare a sodium hydroxide solution for standby use.
[0093] The water-soaked corn cobs were immersed in a sodium hydroxide solution, and treated for 60 seconds at a microwave power of 100 W, followed by a 30-second break, and the microwave treatment was repeated once; then the corn cobs were allowed to stand and soak for 1 hour.
[0094] After taking out, dry in hot air to obtain alkaline soaked corn cob.
[0095] Step d: crushing the alkaline soaked corn cob to obtain corn cob particles, wherein the particle size of the corn cob particles is controlled to be 2-4 mm.
[0096] The present application also provides a method for preparing self-compacting concrete, comprising the following steps:
[0097] Step 1: Mix sisal fiber, corncob particles and sodium alginate at 650 r / min and stir until uniform to obtain a mixture.
[0098] Step 2: Mix cement, mineral admixture, mixture and water, and stir until uniform to obtain a first mixture.
[0099] Step 3: Mix the fine aggregate with the first mixture and stir until uniform.
[0100] Then continue to add coarse aggregate and mix until uniform to obtain the second mixture.
[0101] Step 4: Mix the second mixture with the admixture and stir until uniform to obtain self-compacting concrete.
[0102] Example 4
[0103] A self-compacting concrete, which is different from Example 1 in that the specific amounts of various raw materials are different, as shown in Table 1 for details.
[0104] Example 5
[0105] A self-compacting concrete, which is different from Example 1 in that the specific amounts of various raw materials are different, as shown in Table 1 for details.
[0106] Table 1
[0107]
[0108]
[0109] Example 6
[0110] A self-compacting concrete, which is different from Example 1 in that:
[0111] The corncob particles used in this embodiment are prepared by the following steps:
[0112] Step a: soak corn cobs in water with a mass ratio of corn cobs to water of 1:5 for 2 hours, take them out and dry them in hot air to obtain water-soaked corn cobs.
[0113] Step b: weighing the alkali according to the mass ratio of the water-soaked corncob to the alkali being 1:0.03. In this embodiment, the alkali is sodium hydroxide.
[0114] Weigh water according to the ratio of 1:1 between the mass of soaked corn cobs and water, and dilute the alkali and water to prepare a sodium hydroxide solution for standby use.
[0115] The water-soaked corn cobs were immersed in a sodium hydroxide solution, and treated at a microwave power of 120 W for 45 seconds, with a rest period of 30 seconds, and the microwave treatment was repeated twice; and then the corn cobs were allowed to stand and soak for 1.5 hours.
[0116] After taking out, dry in hot air to obtain alkaline soaked corn cob.
[0117] Step c: crushing the alkaline soaked corn cobs to obtain corn cob particles, wherein the particle size of the corn cob particles is controlled to be 2-4 mm.
[0118] Example 7
[0119] A self-compacting concrete, which is different from Example 1 in that:
[0120] The corncob particles used in this embodiment are prepared by the following steps:
[0121] Step a: calcining corn cobs at 250° C. for 40 minutes to obtain calcined corn cobs.
[0122] Step b: weighing the alkali according to the mass ratio of calcined corncob to alkali of 1:0.03. In this embodiment, the alkali is sodium hydroxide.
[0123] Weigh water according to the ratio of calcined corn cob to water in a ratio of 1:1, and dilute the alkali and water to prepare a sodium hydroxide solution for standby use.
[0124] The calcined corn cobs were soaked in a sodium hydroxide solution and treated at a microwave power of 120 W for 45 seconds, followed by a 30-second break, and the microwave treatment was repeated twice; the solution was then allowed to stand and soak for 1.5 hours.
[0125] After taking out, dry in hot air to obtain alkaline soaked corn cob.
[0126] Step c: crushing the alkaline soaked corn cobs to obtain corn cob particles, wherein the particle size of the corn cob particles is controlled to be 2-4 mm.
[0127] Example 8
[0128] A self-compacting concrete, which is different from Example 1 in that:
[0129] The corncob particles used in this embodiment are prepared by the following steps:
[0130] Step a: calcining corn cobs at 250° C. for 40 minutes to obtain calcined corn cobs.
[0131] Step b: soaking the calcined corn cobs in water, with the mass ratio of calcined corn cobs to water being 1:5, soaking for 2 hours, taking out and drying in hot air to obtain water-soaked corn cobs.
[0132] Step c: crushing the soaked corncobs to obtain corncob particles, wherein the particle size of the corncob particles is controlled to be 2-4 mm.
[0133] Example 9
[0134] A self-compacting concrete, which is different from Example 1 in that:
[0135] The corncob particles used in this embodiment are prepared by the following steps:
[0136] Step a: calcining corn cobs at 250° C. for 40 minutes to obtain calcined corn cobs.
[0137] Step b: soaking the calcined corn cobs in water, with the mass ratio of calcined corn cobs to water being 1:5, soaking for 2 hours, taking out and drying in hot air to obtain water-soaked corn cobs.
[0138] Step c: weighing the alkali according to the mass ratio of the water-soaked corncob to the alkali being 1:0.03. In this embodiment, the alkali is sodium hydroxide.
[0139] Weigh water according to the ratio of 1:1 between the mass of soaked corn cobs and water, and dilute the alkali and water to prepare a sodium hydroxide solution for standby use.
[0140] Soak the water-soaked corn cobs in a sodium hydroxide solution for 2 hours, take them out and dry them in hot air to obtain alkaline-soaked corn cobs.
[0141] Step d: crushing the alkaline soaked corn cob to obtain corn cob particles, wherein the particle size of the corn cob particles is controlled to be 2-4 mm.
[0142] Example 10
[0143] A self-compacting concrete, which is different from Example 1 in that:
[0144] The corncob particles are prepared by the following steps: crushing commercially available corncobs to obtain corncob particles, and the particle size of the corncob particles is controlled at 2-4 mm.
[0145] Comparative Example
[0146] Comparative Example 1
[0147] A self-compacting concrete, which is different from Example 1 in that sisal fiber is replaced by bamboo fiber.
[0148] Comparative Example 2
[0149] A self-compacting concrete, which is different from Example 1 in that corncob particles are omitted.
[0150] Comparative Example 3
[0151] A self-compacting concrete, which is different from Example 1 in that sodium alginate is omitted.
[0152] Comparative Example 4
[0153] A self-compacting concrete, which is different from Example 1 in that: sisal fiber is 20 kg, corn cob particles are 5 kg, and sodium alginate is 0.5 kg.
[0154] Comparative Example 5
[0155] A self-compacting concrete, which is different from Example 1 in that sisal fiber, corncob particles and sodium alginate are omitted.
[0156] Performance testing
[0157] 1. Compressive strength: Referring to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the self-compacting concrete of Examples 1-10 and Comparative Examples 1-5 was tested for 28d compressive strength, and the results are recorded in Table 2.
[0158] 2. Fluidity: The slump of the self-compacting concrete of Examples 1-10 and Comparative Examples 1-5 was tested with reference to JGJ / T 283-2012 "Technical Specification for Application of Self-compacting Concrete", and the results are recorded in Table 2.
[0159] 3. Anti-segregation:
[0160] (1) The self-compacting concrete of Examples 1-10 and Comparative Examples 1-5 were tested with reference to JGJ / T 283-2012 "Technical Specification for Application of Self-compacting Concrete".
[0161] The L-type test H2 / H1 (H2 represents the height of concrete at the far end of the L-type rear groove, and H1 represents the height of concrete at the near end of the L-type rear groove) index reflects the gap passability and anti-segregation performance.
[0162] The results are recorded in Table 2.
[0163] (2) With reference to JGJ / T 283-2012 "Technical Specification for Application of Self-compacting Concrete", the self-compacting concrete of Examples 1-10 and Comparative Examples 1-5 were tested using the sieve analysis method.
[0164] The results are recorded in Table 2.
[0165] Table 2
[0166]
[0167]
[0168] Comparative Example 5 omits sisal fiber, corncob particles, and sodium alginate, and is closest to commercially available concrete. According to the test data in Table 2, the concretes of Examples 1-10 have higher compressive strength, better fluidity, and better segregation resistance than those of Comparative Example 5, indicating that the technical solution provided by the present application can indeed effectively improve the strength, fluidity, and segregation resistance of concrete.
[0169] Comparative Examples 1-3 are based on Example 1, and any of sisal fiber, corncob particles, and sodium alginate are replaced or omitted; Comparative Example 4 is based on Example 1, and the dosage of sisal fiber, corncob particles, and sodium alginate in the system is changed. The concretes prepared in Comparative Examples 1-4 have performance gaps with those in Example 1 in terms of strength, fluidity, and segregation resistance. It is worth mentioning that the dosage of sisal fiber is increased in Comparative Example 4, so the compressive strength is higher, but the fluidity and segregation resistance are not good.
[0170] This shows that sisal fiber, corncob particles and sodium alginate have special coordination effects in the system, and none of them can be missing, forming an organic whole.
[0171] Example 10 is based on Example 1, but corn cobs are not subjected to much treatment, which is equivalent to the preparation method of directly using corn cobs on the market. According to the test data in Table 2, it can be seen that due to the hollow structure of corn cobs, sisal fiber and sodium alginate have a certain coordination effect with it, but due to the presence of impurities such as polysaccharides, the coordination effect cannot be fully exerted, resulting in a decrease in strength, fluidity, and anti-segregation properties.
[0172] Examples 6-9 are based on Example 1, but the processing method of the corn cob particles is changed, the morphology of the corn cob particles is changed, and the coordination effect with sisal fiber and sodium alginate in the system is also changed.
[0173] This indicates that the special preparation of corncob particles can improve the performance of concrete. If the special preparation process can be further defined, the degree of improvement will be even greater.
[0174] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A self-compacting concrete, characterized in that: The raw materials include the following in parts by weight: 235-260 parts of cement, 120-160 parts of mineral admixture, 750-800 parts of fine aggregate, 1000-1200 parts of coarse aggregate, 5-10 parts of admixture, 148-160 parts of water, 5-10 parts of sisal fiber, 10-20 parts of corn cob particles, and 1-5 parts of sodium alginate; The method for processing the corncob particles comprises the following steps: Step a: treating corn cobs at 200-300° C. for 30-60 min to obtain calcined corn cobs; Step b: soaking the calcined corn cobs in water to obtain water-soaked corn cobs; Step c: soaking the water-soaked corn cobs in an alkaline solution to obtain alkaline-soaked corn cobs; Step d: crushing the alkali-soaked corn cobs to obtain corn cob particles.
2. The self-compacting concrete according to claim 1, characterized in that: The self-compacting concrete comprises the following raw materials in parts by weight: 245-255 parts of cement, 130-145 parts of mineral admixture, 765-780 parts of fine aggregate, 1000-1100 parts of coarse aggregate, 7-9 parts of admixture, 150-158 parts of water, 6.5-8 parts of sisal fiber, 13.5-18 parts of corn cob particles, and 1.5-3.5 parts of sodium alginate.
3. The self-compacting concrete according to claim 1, characterized in that: The particle size of the corncob particles is 2-4 mm.
4. The self-compacting concrete according to claim 1, characterized in that: In the step c, when the water-soaked corn cobs are soaked in an alkaline solution, the corn cobs are treated for 30-60 seconds under a microwave power of 100-150 W, with a rest period of 30 seconds, and the microwave treatment is repeated 1-2 times; and then the corn cobs are allowed to stand and soak for 1-2 hours to obtain alkaline-soaked corn cobs.
5. The self-compacting concrete according to claim 1, characterized in that: The mass ratio of the water-soaked corn cob to the alkali in the alkali solution is 1:(0.01-0.05).
6. A method for preparing the self-compacting concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: Mix cement, mineral admixture, sisal fiber, corncob particles, sodium alginate and water until uniform to obtain a first mixture; Step 2: Mix the fine aggregate with the first mixture, and then add the coarse aggregate and mix until uniform to obtain the second mixture; Step 3: Mix the second mixture with the admixture until uniform to obtain self-compacting concrete.
7. The method for preparing self-compacting concrete according to claim 6, characterized in that: The sisal fiber, corncob particles and sodium alginate are mixed at 650-750 r / min until uniform, to obtain a mixture; the mixture is mixed with cement, mineral admixture and water until uniform, to obtain a first mixture.
Citation Information
Patent Citations
Biomass aggregate recycled concrete and preparation method thereof
CN110922143A
Self-compacting concrete and preparation method thereof
CN116573895A